RISK FACTORS FOR POSTOPERATIVE OSTEOMYELITIS AMONG PATIENTS AFTER BONE FRACTURE: A MATCHED CASE–CONTROL STUDY - Slyamova, Gulnur; Gusmanov, Arnur; Batpenov, Arman; Kaliev, Nurlan; Viderman, Dmitriy (Journal of Clinical Medicine, 2022)
The healthcare burden of osteomyelitis is increasing. Postoperative and posttraumatic osteomyelitis account for 80% of all cases of osteomyelitis. The aim of this study was to find risk factors for postoperative osteomyelitis in Kazakhstan. We included 245 patients admitted to the National Scientific Center of Traumatology and Orthopedics from 2018 to 2020. Cases were matched with controls in a 1:4 ratio. Exact matching was performed by gender, ICD-10, and ICD-9 codes. The main variables included socio-demographics, diagnosis at admission, characteristics of fractures, comorbidities, complications, hospitalization milestones, and osteomyelitis characteristics. Descriptive analyses, along with bivariate analysis and multivariate conditional logistic regression, were performed. Open fracture (adjOR = 6.25; 95%CI 1.64–23.79), the presence of complications of initial fracture (adjOR = 3.46, 95%CI 1.13–10.56), comminuted fracture form (adjOR = 1.87; 95%CI 0.73–4.75), a positive history of diabetes or blood glucose >7 g/L (adjOR = 4.25; 95%CI 1.26–14.3), incision or wound length of more than 10 cm (adjOR = 6.53; 95%CI 1.1–38.6), additional implanted medical item (adjOR = 1.23; 95% CI 1.1–1.47), and unemployment or being retired (adjOR = 4.21; 95%CI 1.74–10.18) were found to be significant predictors of postoperative osteomyelitis. Almost all our findings are concordant with previous studies, except for the type of fracture. Different authors report conflicting results on the latter potential risk factor. Therefore, prospective studies on this issue are required.
Keywords: Type of access: Open Access; osteomyelitis; risk factors; postoperative complications; infection; outcomes